1994
DOI: 10.1038/368332a0
|View full text |Cite
|
Sign up to set email alerts
|

Unusual permeability properties of gastric gland cells

Abstract: Physiologists have long pondered the riddle of why the stomach is itself not digested by the very juice it secretes. One explanation is that a mucus-bicarbonate barrier, coating the stomach lumen as well as superficial portions of gastric glands, prevents autodigestion. However, this leaves unanswered the question of what protects cells deeper in the glands, which seem to lack a mucus barrier. These are the parietal and chief cells, which secrete acid and pepsin. Using perfused single gastric glands from rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
129
1
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(133 citation statements)
references
References 15 publications
2
129
1
1
Order By: Relevance
“…Bar = 100 microns experimentation as reviewed by Endeward et al (2014). Approximately 2 decades 269 ago, research using a single stomach gland demonstrated that while CO2 was 270 transported across basal membranes as rapidly as might be predicted by the theory of 271 "free movement," transport across the apical membrane (Waisbren et al 1994) was 272 at least two orders of magnitude slower. Similarly, Endeward and Gros (2013) 273 demonstrated that CO2 permeability for guinea pig colon membrane is more than 100 274 times slower than CO2 permeability for human red cells.…”
mentioning
confidence: 99%
“…Bar = 100 microns experimentation as reviewed by Endeward et al (2014). Approximately 2 decades 269 ago, research using a single stomach gland demonstrated that while CO2 was 270 transported across basal membranes as rapidly as might be predicted by the theory of 271 "free movement," transport across the apical membrane (Waisbren et al 1994) was 272 at least two orders of magnitude slower. Similarly, Endeward and Gros (2013) 273 demonstrated that CO2 permeability for guinea pig colon membrane is more than 100 274 times slower than CO2 permeability for human red cells.…”
mentioning
confidence: 99%
“…pH i was measured with the fluorescent dye BCECF and a digital imaging system. Data from reference (24). Ϫ by using active-transport processes to secrete H ϩ into the tubule lumen and titrating HCO 3 Ϫ to CO 2 and H 2 O.…”
Section: Membranes With Negligible Gas Permeabilitymentioning
confidence: 99%
“…Gross movement of O 2 and CO 2 across the lung has been measured, as has NH 3 permeability of some membranes (5)(6)(7). Although it has been accepted that gases are freely permeable across membranes, rapid flux of gases across some membranes would upset carefully regulated electrolyte concentrations.…”
mentioning
confidence: 99%